Impact of fancy job titles on recruitment success. - Hang, Mui Cheng. (2008)
Given high costs in recruitment, better understanding of whether job titles affects recruitment success can help mgrs attract/retain best workforce effectively. In this experiment, subjects are given either a fancy job title or a traditional job title advertisement for a job to determine if there were any differences in perceptions.